Language, Power, and Resistance : Mainstreaming Deaf Education - Mathews, Elizabeth S. (Gallaudet University Press, 2017)
"The current policy of educating deaf and hard of hearing students in a mainstream setting, rather than in the segregated environments of deaf schools, has been portrayed as a positive step. Author explores this claim through qualitative research with DHH children in the Republic of Ireland"--